Novel approaches to the isolation of farm animal embryonic stem cells - Thansa, Kwanta (2009)
The establishment of stable immortal ES cell lines using embryos as a source of isolation in domesticated farm animals, in particular for pigs, which are closer to humans than other ungulates, has not been reported; hence this information could contribute to the improvement of regenerative medicine in humans, biotechnology and agriculture. Therefore, the discovery of effective protocols to derive and maintain ES cells and the induction of purified somatic cells from ES cells in pigs is of importance. The objectives of this study were to produce pES-like cells and direct differentiation of the ES-like cells obtained by improving the culture conditions. In vivo-derived porcine blastocysts at day 6-8 were classified into two groups distinguished by the exhibition of ICMs and epiblasts of the embryos. In each group, intact blastocysts and isolated ICMs or epiblasts were designed to culture in either KO4bh or DM40bh medium on mitotically inactivated MEFs under the humidified air of 5%CO2 at 39°C until the primary outgrowth of ES-like cells was observed. Two morphologically distinct pES-like cells, pESA-like and pESB-like cells were isolated from the epiblasts, whereas no cell lines were generated from ICMs. pESA-like cells were observed as individual small round cells containing one or multiple nucleoli along with a high ratio of nucleus to cytoplasm, while pESB-like cells formed dome-like colonies. The pESA-like cells were stained both negative and positive with the alkaline phosphatase enzyme, while pESB-like cells were all stained positive. With immunofluorescence staining of OCT-4 and nanog, the nuclei of pESB-like cells appeared not to be stained positive with these two antibodies, while the designed self-renewing genes such as OCT-4, nanog, SOX-2, REX-1 and DPPA-3 were detectable as similar to mES cells. Regarding the pluripotent abilities of pESB-like cells, they could be induced to form neuronal-like, neuronal supporting-like, smooth muscle-like and hepatic-like cells in a variety of desirable differentiation media under the feeder-free culture system. The cytoplasmic contents of certain induced mature cells were stained positive with nestin, α-smooth muscle actin and α-fetoprotein in association with the expression of differentiated genes specific to each germ layer such as nestin, α-smooth muscle actin, smooth muscle myosin heavy chain, α-cardiac actin, transthyretin, α-fetoprotein, albumin and HGF1β. In conclusion, pESB-like cells obtained in this study may possibly have the potential to be authentic ES cells isolated from early epiblast origin as mES cells.